Asites dan Hypoalbuinemia Pada Kucing Mix Domestic Long Hair - Era Hari Mudji Restijono; Palestin Djazuli; Kurnia Desiandura; Hana Cipka Pramuda Wardhani (Acta VETERINARIA Indonesiana, 2022)
Ascites is a clinical manifestation of a disease with fluid leaking into the abdominal cavity either transudate or exudate. Cat has symptoms of abdominal distension and pallor of the gingival mucosa but the general condition is still good. Paracentesis is performed to remove fluid and perform fluid checks as well as blood and blood chemistry tests to support the diagnosis. The fluid released is in the form of a transudate (clear and liquid), blood examination reveals anemia, blood chemistry examination only shows a low albumin level (hypoalbuminemia), then the diagnosis is established ascites due to hypoalbuminemia. Mola's cat was hospitalized with diuretic therapy (furosemide), Hematodin® injection, Catosal® injection, albumin supplement (Fibumin), Hepacartine supplement, Amoxicillin and Clavulanate Potassium antibiotics, and anti-inflammatory and antipyretic Tolfenamic Acid and paracentesis (puncture). During the hospitalization showed progress in the cat, the decrease in fluid was marked by a decrease in the size of the abdomen in the cat, although it took a long time. There was no deterioration in the condition during hospitalization. The fever that appears can be controlled by giving tolfenamic acid and the temperature is still normal until now.